Characterization of mesoscale geometrical features of a preform using spectral Moiré analysis on pressure print. (November 2021) - Bancora, S.; Binetruy, C.; Advani, S.; Comas-Cardona, S.
Abstract: In the frame of LCM processes, the mesoscopic architecture of a preform is defined by the sequential stacking of layers in the mold. Once the compaction is carried out, the precise orientation of layers and spatial distribution of tows is difficult to know with precision. The lack of this information can lead to a wrong prediction of properties. In this work, we present a new non-destructive methodology to obtain information about the mesoscale architecture of a multi-layer preform in its compacted state. Using a flexible pressure-sensitive film, the compaction pressure field is captured. Data is analyzed using spectral Moiré theory to retrieve the orientation and spatial distribution of tows for each layer in the stack. This technique is non-destructive and scalable in size, making it suitable to characterize large preforms before infusion. The methodology is detailed and tested over a varying number of layers and configurations. Graphical abstract: